Cap 1 Messenger RNA Synthesis with Co‐transcriptional CleanCap® Analog by In Vitro Transcription. Issue 2 (1st February 2021) - Henderson, Jordana M.; Ujita, Andrew; Hill, Elizabeth; Yousif‐Rosales, Sally; Smith, Cory; Ko, Nicholas; McReynolds, Taylor; Cabral, Charles R.; Escamilla‐Powers, Julienne R.; Houston, Michael E.
Abstract: Synthetic messenger RNA (mRNA)−based therapeutics are an increasingly popular approach to gene and cell therapies, genome engineering, enzyme replacement therapy, and now, during the global SARS‐CoV‐2 pandemic, vaccine development. mRNA for such purposes can be synthesized through an enzymatic in vitro transcription (IVT) reaction and formulated for in vivo delivery. Mature mRNA requires a 5′‐cap for gene expression and mRNA stability. There are two methods to add a cap in vitro: via a two‐step multi‐enzymatic reaction or co‐transcriptionally. Co‐transcriptional methods minimize reaction steps and enzymes needed to make mRNA when compared to enzymatic capping. CleanCap ® AG co‐transcriptional capping results in 5 mg/ml of IVT with 94% 5′‐cap 1 structure. This is highly efficient compared to first‐generation cap analogs, such as mCap and ARCA, that incorporate cap 0 structures at lower efficiency and reaction yield. This article describes co‐transcriptional capping using TriLink Biotechnology's CleanCap ® AG in IVT. © 2021 The Authors. This article was corrected on 22 November 2021. See the end of the full text for details. Basic Protocol 1 : IVT with CleanCap Basic Protocol 2 : mRNA purification and analysis